Prodigiosin found in Serratia marcescens y2 initiates phototoxicity in the cytomembrane - Wang, Fei; Luo, Hailan; Song, Guohua; Liu, Chang; Wang, Jianguo; Xu, Jingliang; Su, Xiuhong; Ma, Xuyuan (Electronic Journal of Biotechnology, 2013)
Background: Light can be absorbed by bacterial pigment and affects its growth. Prodigiosin is a red pigment found in various bacterial species. The purpose of this study was to investigate the impacts of light on prodigiosin production, biomass formation, and membrane integrity of Serratia marcescens y2. Results: S. marcescens y2 grew better and produced more intracellular prodigiosin in darkness than in illumination. The pigment leakage ratio from cells was detected more in light than in darkness conditions. Ethidium bromide uptake assay could visually prove the prodigiosin-related loss of membrane integrity under illumination. A higher concentration of malondialdehyde (MDA) was detected in light-treated culture than in darkness. Tests of different light treatments (red, yellow, blue and green) showed that the maximum extracellular pigment and the minimum biomass formation and intracellular pigment were obtained in green light. Conclusions: Prodigiosin could absorb light, and then initiate phototoxicity damage of the cytomembrane.